Biallelic mutation of MSH2 in primary human cells is associated with sensitivity to irradiation and altered RAD51 foci kinetics. Issue 8 (4th May 2007) - Barwell, J; Pangon, L; Hodgson, S; Georgiou, A; Kesterton, I; Slade, T; Taylor, M; Payne, S J; Brinkman, H; Smythe, J; Sebire, N J; Solomon, E; et al.
Abstract : Background: Reports of differential mutagen sensitivity conferred by a defect in the mismatch repair (MMR) pathway are inconsistent in their conclusions. Previous studies have investigated cells established from immortalised human colorectal tumour lines or cells from animal models. Methods: We examined primary human MSH2-deficient neonatal cells, bearing a biallelic truncating mutation in MSH2, for viability and chromosomal damage after exposure to DNA-damaging agents. Results: MSH2-deficient cells exhibit no response to interstrand DNA cross-linking agents but do show reduced viability in response to irradiation. They also show increased chromosome damage and exhibit altered RAD51 foci kinetics after irradiation exposure, indicating defective homologous recombinational repair. Discussion: The cellular features and sensitivity of MSH2-deficient primary human cells are broadly in agreement with observations of primary murine cells lacking the same gene. The data therefore support the view that the murine model recapitulates early features of MMR deficiency in humans, and implies that the variable data reported for MMR-deficient immortalised human cells may be due to further genetic or epigenetic lesions. We suggest caution in the use of radiotherapy for treatment of malignancies in individuals with functional loss of MSH2.